2006
DOI: 10.1055/s-2006-926423
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Three-Component Reaction of Triphenylphosphine, DMAD, and Electron-Deficient Styrenes: Facile Synthesis of Cyclopentenyl Phosphoranes

Abstract: The zwitterion formed from triphenylphosphine and DMAD adds to electron-deficient styrenes to form stable cyclopentenyl phosphoranes. This is the first example of such a zwitterion in which the phosphine is incorporated into the product Ever since the pioneering work of Horner, 1 the zwitterion derived from triphenylphosphine and DMAD has been the subject of several investigations. 2 Following the early work of Winterfeldt, 3 Nozaki et al. have shown that the zwitterion reacts with activated carbonyl compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…The phosphorane (159) can be oxidized by a methanolic solution of cerium (IV) ammonium nitrate (CAN) in an oxygen atmosphere. A mechanistic rationale for the formation of phosphorane (159) may be outlined as follows: Initially formed zwitterionic intermediate (3) from the reaction of (1) and (2) adds to the activated styrene (158) in a Michael fashion to yield a betaine (161); latter on cyclization and subsequent deprotonation can deliver the phosphorane (159) (Scheme 43) [170].…”
Section: Route Amentioning
confidence: 99%
See 3 more Smart Citations
“…The phosphorane (159) can be oxidized by a methanolic solution of cerium (IV) ammonium nitrate (CAN) in an oxygen atmosphere. A mechanistic rationale for the formation of phosphorane (159) may be outlined as follows: Initially formed zwitterionic intermediate (3) from the reaction of (1) and (2) adds to the activated styrene (158) in a Michael fashion to yield a betaine (161); latter on cyclization and subsequent deprotonation can deliver the phosphorane (159) (Scheme 43) [170].…”
Section: Route Amentioning
confidence: 99%
“…Stable crystalline phosphorus ylides (171) are obtained in excellent yields from the 1:1:2 addition reaction between trialkyl phosphites (170) and (2) in the presence of arylsulfonyl isocyanates (167). On the basis of the well established chemistry of trivalent phosphorus nucleophiles, it is reasonable to propose that phosphorane (171) results from initial addition of trialkyl phosphite (170) to the acetylenic ester (2) and subsequent attack of the resulting zwitterion (172) on the arylsulfonyl isocyanate (167) to yield betaine (173).…”
Section: Route Amentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18] We have also demonstrated that the activated carbonyl of phenyl glyoxalate and isatin derivatives can take part in such reactions successfully, thus constituting a ready synthesis of heterocyclic compounds. [19][20] We now wish to report a simple one-pot three-component reaction between dialkyl acetylenedicarboxylates, Ph3P, and benzofuran-2,3-dione derivatives leading to methyl 4'-methoxy-spiro[benzofuran-3,2'-furan]-2,5'-dione-3'-carboxylate derivatives as γ-spirolactone systems (Scheme 2 and Table 1 …”
Section: Methodsmentioning
confidence: 88%